GOOD CORPORATE GOVERNANCE, AUDIT QUALITY, DAN EARNINGS QUALITY DI PERUSAHAAN MANUFAKTUR - Angela Marchelia Santoso; Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to examine the influence of managerial ownership, institutional ownership, and commissioner board structure toward earnings quality with a moderating effect study from audit quality in manufacturing companies listing in the Indonesian Stock Exchange in the periode 2017-2019. The sample was determined by purposive sampling method. The research conducted by taking 86 manufacturing companies. The result of this research shows that commissioner board structure have negative effect on earnings quality, while managerial ownership, institutional ownership, and managerial ownership moderated by audit quality have no effect on earnings quality.